Analysis of the Utilization of Illegal Educational Sites from an Islamic and Positive Law Perspective - Hamidah, Aam Siti; Pranawa, Evan; Robbiyanto, Robbiyanto (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
This study aims to find out the various perceptionof students regarding the use of ilegal sites in education when viewed from the prespective of islam and positif law, given that the number of users of illegal sites is widespread, both by the public and intelectuals. The method used in this research is a quantitative research method by conducting a survey through questionnaries distributed through google forms media. Based on the result of the research and the answers from the respondents, it can be concluced that the use of illegal sites, ecpecially in education, is indeed not recommended both from a levat prespective and the reception of each respondent. However, if you look at illegal sites in education based on positive law, which means it has benefits in it, then the islamic prespective itself raises the term istihsan to be used as a reference. In other words, the benefits or positive values that can bee taken from the use of these illegal sites in the world of education are permissible based on the islamic prespective of Istihsan Bil ’Urf with a note within reasonable limits. Keywords : Illegal site, Islamic perspective and positive law